Power Production and Drag of Autorotating Cross Cylinder Turbine Models - Rachmadian Wulandana; David Foote; Seth Pearl; Nataniel Ilyayev (Institute for Research on Innovation and Industrial System (IRIS), 2022)
The autorotation phenomena of bladeless symmetric objects exposed to fluid flow have promised power generation from the kinetic energy of natural water and air currents. Our past experiments on bladeless turbine models suggest non-linear correlation between the flow speed and power production. This report explores factors such as flow obstacles and turbine’s position that may affect the power generation of such turbines at Reynolds numbers around 10,000 to 50,000. Using a custom-made water flow tank, we tested the power production and generated drag forces of 3D-printed bladeless turbine models under various conditions of flow. Results indicate the significant effect of flow straightener and flow perturbation to the power production. Additionally, the effects of turbine infill density and flow speed on the generated drag and measured rotation-per-minute (rpm) are reported. The minimal effects from the turbine’s weight and position in the water flow on the power production require further exploration